Ultrastructural insights of postsynaptic glutamate receptor organization - Fukazawa, Yugo; Tarusawa, Etsuko; Matsui, Ko; Ryuichi Shigemoto (Tanpakushitsu kakusan koso Protein nucleic acid enzyme)

Dendritic Ih ensures high-fidelity dendritic spike responses of motion-sensitive neurons in rat superior colliculus - Endo, Toshiaki; Tarusawa, Etsuko; Notomi, Takuya; Kaneda, Katsuyuki; Hirabayashi, Masumi; Ryuichi Shigemoto; Isa, Tadashi (Journal of Neurophysiology)
Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels that generate Ih currents are widely distributed in the brain and have been shown to contribute to various neuronal functions. In the present study, we investigated the functions of Ih in the motion-sensitive projection neurons [wide field vertical (WFV) cells] of the superior colliculus, a pivotal visual center for detection of and orientating to salient objects. Combination of whole cell recordings and immunohistochemical investigations suggested that HCN1 channels dominantly contribute to the Ih in WFV cells among HCN isoforms expressed in the superficial superior colliculus and mainly located on their expansive dendritic trees. We found that blocking Ih suppressed the initiation of short- and fixed-latency dendritic spike responses and led instead to long- and fluctuating-latency somatic spike responses to optic fiber stimulations. These results suggest that the dendritic Ih facilitates the dendritic initiation and/or propagation of action potentials and ensures that WFV cells generate spike responses to distal synaptic inputs in a sensitive and robustly time-locked manner, probably by acting as continuous depolarizing drive and fixing dendritic membrane potentials close to the spike threshold. These functions are different from known functions of dendritic Ih revealed in hippocampal and neocortical pyramidal cells, where they spatiotemporally limit the propagations of synaptic inputs along the apical dendrites by reducing dendritic membrane resistance. Thus we have revealed new functional aspects of Ih, and these dendritic properties are likely critical for visual motion processing in these neurons.

Right isomerism of the brain in inversus viscerum mutant mice - Kawakami, Ryosuke; Dobi, Alice; Ryuichi Shigemoto; Ito, Isao (PLoS One)
Left-right (L-R) asymmetry is a fundamental feature of higher-order neural function. However, the molecular basis of brain asymmetry remains unclear. We recently reported L-R asymmetry of hippocampal circuitry caused by differential allocation of N-methyl-O-aspartate receptor (NMDAR) subunit GluRε2 (NR2B) in hippocambal synapses. Using electrophysiology and immunocytochemistry, here we analyzed the hippocampal circuitry of the inversus viscerum (iv) mouse that has a randomized laterality of internal organs. The iv mouse hippocampus lacks L-R asymmetry, it exhibits right isomerism in the synaptic distribution of the ε2 subunit, irrespective of the laterality of visceral organs. This independent right isomerism of the hippocampus is the first evidence that a distinct mechanism downstream of the iv mutation generates brain asymmetry.

The presence of pacemaker HCN channels identifies theta rhythmic GABAergic neurons in the medial septum - Varga, Viktor; Hangya, Balázs; Kránitz, Kinga; Ludányi, Anikó; Zemankovics, Rita; Katona, István; Ryuichi Shigemoto; Freund, Tamás F; Borhegyi, Zsolt (Journal of Physiology)
The medial septum (MS) is an indispensable component of the subcortical network which synchronizes the hippocampus at theta frequency during specific stages of information processing. GABAergic neurons exhibiting highly regular firing coupled to the hippocampal theta rhythm are thought to form the core of the MS rhythm-generating network. In recent studies the hyperpolarization-activated, cyclic nucleotide-gated non-selective cation (HCN) channel was shown to participate in theta synchronization of the medial septum. Here, we tested the hypothesis that HCN channel expression correlates with theta modulated firing behaviour of MS neurons by a combined anatomical and electrophysiological approach. HCN-expressing neurons represented a subpopulation of GABAergic cells in the MS partly overlapping with parvalbumin (PV)-containing neurons. Rhythmic firing in the theta frequency range was characteristic of all HCN-expressing neurons. In contrast, only a minority of HCN-negative cells displayed theta related activity. All HCN cells had tight phase coupling to hippocampal theta waves. As a group, PV-expressing HCN neurons had a marked bimodal phase distribution, whereas PV-immunonegative HCN neurons did not show group-level phase preference despite significant individual phase coupling. Microiontophoretic blockade of HCN channels resulted in the reduction of discharge frequency, but theta rhythmic firing was perturbed only in a few cases. Our data imply that HCN-expressing GABAergic neurons provide rhythmic drive in all phases of the hippocampal theta activity. In most MS theta cells rhythm genesis is apparently determined by interactions at the level of the network rather than by the pacemaking property of HCN channels alone.

Connexin45-containing neuronal gap junctions in rodent retina also contain connexin36 in both apposing hemiplaques, forming bihomotypic gap junctions, with scaffolding contributed by zonula occludens-1 - Li, Xinbo; Kamasawa, Naomi; Ciolofan, Cristina; Olson, Carl O; Lu, Shijun; Davidson, Kimberly G; Yasumura, Thomas; Ryuichi Shigemoto; Rash, John E; Nagy, James I (Journal of Neuroscience)
Mammalian retinas contain abundant neuronal gap junctions, particularly in the inner plexiform layer (IPL), where the two principal neuronal connexin proteins are Cx36 and Cx45. Currently undetermined are coupling relationships between these connexins and whether both are expressed together or separately in a neuronal subtype-specific manner. Although Cx45-expressing neurons strongly couple with Cx36-expressing neurons, possibly via heterotypic gap junctions, Cx45 and Cx36 failed to form functional heterotypic channels in vitro. We now show that Cx36 and Cx45 coexpressed in HeLa cells were colocalized in immunofluorescent puncta between contacting cells, demonstrating targeting/scaffolding competence for both connexins in vitro. However, Cx36 and Cx45 expressed separately did not form immunofluorescent puncta containing both connexins, supporting lack of heterotypic coupling competence. In IPL, 87% of Cx45-immunofluorescent puncta were colocalized with Cx36, supporting either widespread heterotypic coupling or bihomotypic coupling. Ultrastructurally, Cx45 was detected in 9% of IPL gap junction hemiplaques, 90-100% of which also contained Cx36, demonstrating connexin coexpression and cotargeting in virtually all IPL neurons that express Cx45. Moreover, double replicas revealed both connexins in separate domains mirrored on both sides of matched hemiplaques. With previous evidence that Cx36 interacts with PDZ1 domain of zonula occludens-1 (ZO-1), we show that Cx45 interacts with PDZ2 domain of ZO-1, and that Cx36, Cx45, and ZO-1 coimmunoprecipitate, suggesting that ZO-1 provides for coscaffolding of Cx45 with Cx36. These data document that in Cx45-expressing neurons of IPL, Cx45 is almost always accompanied by Cx36, forming "bihomotypic" gap junctions, with Cx45 structurally coupling to Cx45 and Cx36 coupling to Cx36.

Numbers, densities, and colocalization of AMPA- and NMDA-type glutamate receptors at individual synapses in the superficial spinal dorsal horn of rats - Antal, Miklós; Fukazawa, Yugo; Eördögh, Mária; Muszil, Dóra; Molnár, Elek; Itakura, Makoto; Takahashi, Masami; Ryuichi Shigemoto (Journal of Neuroscience)
Ionotropic glutamate receptors play important roles in spinal processing of nociceptive sensory signals and induction of central sensitization in chronic pain. Here we applied highly sensitive freeze-fracture replica labeling to laminae I-II of the spinal dorsal horn of rats and investigated the numbers, densities, and colocalization of AMPA- and NMDA-type glutamate receptors at individual postsynaptic membrane specializations with a high resolution. All glutamatergic postsynaptic membranes in laminae I-II expressed AMPA receptors, and most of them (96%) were also immunoreactive for the NR1 subunit of NMDA receptors. The numbers of gold particles for AMPA and NMDA receptors at individual postsynaptic membranes showed a linear correlation with the size of postsynaptic membrane specializations and varied in the range of 8-214 and 5-232 with median values of 37 and 28, whereas their densities varied in the range of 325-3365/μm 2 and 102-2263/μm 2 with median values of 1115/μm 2 and 777/μm 2, respectively. Virtually all (99%) glutamatergic postsynaptic membranes expressed GluR2, and most of them (87%) were also immunoreactive for GluR1. The numbers of gold particles for pan-AMPA, NR1, and GluR2 subunits showed a linear correlation with the size of postsynaptic surface areas. Concerning GluR1, there may be two populations of synapses with high and low GluR1 densities. In synapses larger than 0.1 μm 2, GluR1 subunits were recovered in very low numbers. Differential expression of GluR1 and GluR2 subunits suggests regulation of AMPA receptor subunit composition by presynaptic mechanism.

Left-right asymmetry of the hippocampal synapses with differential subunit allocation of glutamate receptors - Shinohara, Yoshiaki; Hirase, Hajime; Watanabe, Masahiko; Itakura, Makoto; Takahashi, Masami; Ryuichi Shigemoto (PNAS)
Left-right asymmetry of the brain has been studied mostly through psychological examination and functional imaging in primates, leaving its molecular and synaptic aspects largely unaddressed. Here, we show that hippocampal CA1 pyramidal cell synapses differ in size, shape, and glutamate receptor expression depending on the laterality of presynaptic origin. CA1 synapses receiving neuronal input from the right CA3 pyramidal cells are larger and have more perforated PSD and a GluR1 expression level twice as high as those receiving input from the left CA3. The synaptic density of GluR1 increases as the size of a synapse increases, whereas that of NR2B decreases because of the relatively constant NR2B expression in CA1 regardless of synapse size. Densities of other major glutamate receptor subunits show no correlation with synapse size, thus resulting in higher net expression in synapses having right input. Our study demonstrates universal left-right asymmetry of hippocampal synapses with a fundamental relationship between synaptic area and the expression of glutamate receptor subunits.

Feynman graphs and renormalization in quantum diffusion - László Erdös; Salmhofer, Manfred; Yau, Horng-Tzer
We review our proof that in a scaling limit, the time evolution of a quantum particle in a static random environment leads to a diffusion equation. In particular, we discuss the role of Feynman graph expansions and of renormalization.

Quantum diffusion of the random Schrödinger evolution in the scaling limit - Erdös, László; Salmhofer, Manfred; Yau, Horng (Acta Mathematica)
We consider random Schrödinger equations on R d for d ≽ 3 with a homogeneous Anderson–Poisson type random potential. Denote by λ the coupling constant and ψt the solution with initial data ψ0 . The space and time variables scale as x∼λ−2−ϰ/2 and t∼λ−2−ϰ with 0<ϰ<ϰ0(d) . We prove that, in the limit λ → 0, the expectation of the Wigner distribution of ψt converges weakly to the solution of a heat equation in the space variable x for arbitrary L 2 initial data. The proof is based on analyzing the phase cancellations of multiple scatterings on the random potential by expanding the propagator into a sum of Feynman graphs. In this paper we consider the non-recollision graphs and prove that the amplitude of the non-ladder diagrams is smaller than their “naive size” by an extra λ c factor per non-(anti)ladder vertex for some c > 0. This is the first rigorous result showing that the improvement over the naive estimates on the Feynman graphs grows as a power of the small parameter with the exponent depending linearly on the number of vertices. This estimate allows us to prove the convergence of the perturbation series.

Rate of decoherence for an electron weakly coupled to a phonon gas - Adami, Riccardo; László Erdös (Journal of Statistical Physics)
We study the dynamics of an electron weakly coupled to a phonon gas. The initial state of the electron is the superposition of two spatially localized distant bumps moving towards each other, and the phonons are in a thermal state. We investigate the dynamics of the system in the kinetic regime and show that the time evolution makes the non-diagonal terms of the density matrix of the electron decay, destroying the interference between the two bumps. We show that such a damping effect is exponential in time, and the related decay rate is proportional to the total scattering cross section of the electron-phonon interaction.

Ground-state energy of a low-density Bose gas: A second-order upper bound - László Erdös; Schlein, Benjamin; Yau, Horng-Tzer (Physical Review A - Atomic, Molecular, and Optical Physics)
Consider N bosons in a finite box Λ= [0,L]3⊂ R3 interacting via a two-body non-negative soft potential V=λ V with V fixed and λ>0 small. We will take the limit L,N→∞ by keeping the density =N/L3 fixed and small. We construct a variational state, which gives an upper bound on the ground-state energy per particle ε, ε≤4πa [1+ (128/15π) (a3) 1/2 Sλ] +O (2 ln ), as →0, with a constant satisfying 1≤ Sλ ≤1+Cλ. Here a is the scattering length of V and thus depends on λ. In comparison, the prediction by Lee and Yang [Phys. Rev. 105, 1119 (1957)] and Lee, Huang, and Yang [Phys. Rev. 106, 1135 (1957)] asserts that Sλ =1 independent of λ.

Repeller or attractor? Selecting the dynamical model for the onset of turbulence in pipe flow - Björn Hof; de Lózar, Alberto; Kuik, Dirk J; Westerweel, Jerry (Physical Review Letters)
The collapse of turbulence, observable in shear flows at low Reynolds numbers, raises the question if turbulence is generically of a transient nature or becomes sustained at some critical point. Recent data have led to conflicting views with the majority of studies supporting the model of turbulence turning into an attracting state. Here we present lifetime measurements of turbulence in pipe flow spanning 8 orders of magnitude in time, drastically extending all previous investigations. We show that no critical point exists in this regime and that in contrast to the prevailing view the turbulent state remains transient. To our knowledge this is the first observation of superexponential transients in turbulence, confirming a conjecture derived from low-dimensional systems.

Networking networks - Azevedo, Ricardo B; Lohaus, Rolf; Tiago Paixao (Evolution & Development)

Role of alternative telomere lengthening unmasked in telomerase knock-out mutant plants - Růčková, Eva; Jirí Friml; Procházková Schrumpfová, Petra; Fajkus, Jiří (Plant Molecular Biology)
Telomeres in many eukaryotes are maintained by telomerase in whose absence telomere shortening occurs. However, telomerase-deficient Arabidopsis thaliana mutants (Attert -/-) show extremely low rates of telomere shortening per plant generation (250-500 bp), which does not correspond to the expected outcome of replicative telomere shortening resulting from ca. 1,000 meristem cell divisions per seed-to-seed generation. To investigate the influence of the number of cell divisions per seed-to-seed generation, Attert -/- mutant plants were propagated from seeds coming either from the lower-most or the upper-most siliques (L- and U-plants) and the length of their telomeres were followed over several generations. The rate of telomere shortening was faster in U-plants, than in L-plants, as would be expected from their higher number of cell divisions per generation. However, this trend was observed only in telomeres whose initial length is relatively high and the differences decreased with progressive general telomere shortening over generations. But in generation 4, the L-plants frequently show a net telomere elongation, while the U-plants fail to do so. We propose that this is due to the activation of alternative telomere lengthening (ALT), a process which is activated in early embryonic development in both U- and L-plants, but is overridden in U-plants due to their higher number of cell divisions per generation. These data demonstrate what so far has only been speculated, that in the absence of telomerase, the number of cell divisions within one generation influences the control of telomere lengths. These results also reveal a fast and efficient activation of ALT mechanism(s) in response to the loss of telomerase activity and imply that ALT is probably involved also in normal plant development.

Auxin transport inhibitors impair vesicle motility and actin cytoskeleton dynamics in diverse eukaryotes - Dhonukshe, Pankaj; Grigoriev, Ilya S; Fischer, Rainer; Tominaga, Motoki; Robinson, David G; Hašek, Jiří; Paciorek, Tomasz; Petrášek, Jan; Seifertová, Daniela; Tejos, Ricardo; Meisel, Lee A; Zažímalová, Eva; et al. (PNAS)
Many aspects of plant development, including patterning and tropisms, are largely dependent on the asymmetric distribution of the plant signaling molecule auxin. Auxin transport inhibitors (ATIs), which interfere with directional auxin transport, have been essential tools in formulating this concept. However, despite the use of ATIs in plant research for many decades, the mechanism of ATI action has remained largely elusive. Using real-time live-cell microscopy, we show here that prominent ATIs such as 2,3,5-triiodobenzoic acid (TIBA) and 2-(1-pyrenoyl) benzoic acid (PBA) inhibit vesicle trafficking in plant, yeast, and mammalian cells. Effects on micropinocytosis, rab5-labeled endosomal motility at the periphery of HeLa cells and on fibroblast mobility indicate that ATIs influence actin cytoskeleton. Visualization of actin cytoskeleton dynamics in plants, yeast, and mammalian cells show that ATIs stabilize actin. Conversely, stabilizing actin by chemical or genetic means interferes with endocytosis, vesicle motility, auxin transport, and plant development, including auxin transport-dependent processes. Our results show that a class of ATIs act as actin stabilizers and advocate that actin-dependent trafficking of auxin transport components participates in the mechanism of auxin transport. These studies also provide an example of how the common eukaryotic process of actin-based vesicle motility can fulfill a plant-specific physiological role.

ARF GEF dependent transcytosis and polar delivery of PIN auxin carriers in Arabidopsis - Kleine-Vehn, Jürgen; Dhonukshe, Pankaj; Sauer, Michael; Brewer, Philip B; Wiśniewska, Justyna; Paciorek, Tomasz; Eva Benková; Jirí Friml (Current Biology)
Cell polarity manifested by the polar cargo delivery to different plasma-membrane domains is a fundamental feature of multicellular organisms. Pathways for polar delivery have been identified in animals; prominent among them is transcytosis, which involves cargo movement between different sides of the cell [1]. PIN transporters are prominent polar cargoes in plants, whose polar subcellular localization determines the directional flow of the signaling molecule auxin [2, 3]. In this study, we address the cellular mechanisms of PIN polar targeting and dynamic polarity changes. We show that apical and basal PIN targeting pathways are interconnected but molecularly distinct by means of ARF GEF vesicle-trafficking regulators. Pharmacological or genetic interference with the Arabidopsis ARF GEF GNOM leads specifically to apicalization of basal cargoes such as PIN1. We visualize the translocation of PIN proteins between the opposite sides of polarized cells in vivo and show that this PIN transcytosis occurs by endocytic recycling and alternative recruitment of the same cargo molecules by apical and basal targeting machineries. Our data suggest that an ARF GEF-dependent transcytosis-like mechanism is operational in plants and provides a plausible mechanism to trigger changes in PIN polarity and hence auxin fluxes during embryogenesis and organogenesis.

Visualization of auxin gradients in embryogenesis - Sauer, Michael; Jirí Friml (Plant Embryogenesis)
Embryogenesis in Arabidopsis thaliana depends on the proper establishment and maintenance of local auxin accumulation. In the course of elucidating the connections between developmental progress and auxin distribution, several techniques have been developed to investigate spatial and temporal distribution of auxin response or accumulation in Arabidopsis embryos. This chapter reviews and describes two independent methods, the detection of the activity of auxin responsive transgenes and immunolocalization of auxin itself.

Plant biology: In their neighbour's shadow - Friml, Jirí; Sauer, Michael (Nature)
They can't move away from shade, so plants resort to a molecular solution to find a place in the sun. The action they take is quite radical, and involves a reprogramming of their development.

In vitro culture of Arabidopsis embryos - Sauer, Michael; Jirí Friml (Plant Embryogenesis)
Embryogenesis of Arabidopsis thaliana follows a nearly invariant cell division pattern and provides an ideal system for studies of early plant development. However, experimental manipulation with embryogenesis is difficult, as the embryo develops deeply inside maternal tissues. Here, we present a method to culture zygotic Arabidopsis embryos in vitro. It enables culturing for prolonged periods of time from the first developmental stages on. The technique omits excision of the embryo by culturing the entire ovule, which facilitates the manual procedure. It allows pharmacological manipulation of embryo development and does not interfere with standard techniques for localizing gene expression and protein localization in the cultivated embryos.

Auxin acts as a local morphogenetic trigger to specify lateral root founder cells - Dubrovsky, Joseph G; Sauer, Michael; Napsucialy-Mendivil, Selene; Ivanchenko, Maria G; Jirí Friml; Shishkova, Svetlana; Celenza, John; Eva Benková (PNAS)
Plants exhibit an exceptional adaptability to different environmental conditions. To a large extent, this adaptability depends on their ability to initiate and form new organs throughout their entire postembryonic life. Plant shoot and root systems unceasingly branch and form axillary shoots or lateral roots, respectively. The first event in the formation of a new organ is specification of founder cells. Several plant hormones, prominent among them auxin, have been implicated in the acquisition of founder cell identity by differentiated cells, but the mechanisms underlying this process are largely elusive. Here, we show that auxin and its local accumulation in root pericycle cells is a necessary and sufficient signal to respecify these cells into lateral root founder cells. Analysis of the alf4-1 mutant suggests that specification of founder cells and the subsequent activation of cell division leading to primordium formation represent two genetically separable events. Time-lapse experiments show that the activation of an auxin response is the earliest detectable event in founder cell specification. Accordingly, local activation of auxin response correlates absolutely with the acquisition of founder cell identity and precedes the actual formation of a lateral root primordium through patterned cell division. Local production and subsequent accumulation of auxin in single pericycle cells induced by Cre-Lox-based activation of auxin synthesis converts them into founder cells. Thus, auxin is the local instructive signal that is sufficient for acquisition of founder cell identity and can be considered a morphogenetic trigger in postembryonic plant organogenesis.